Bernard Hodgson’s Trojan Horse Critique of Neoclassical Economics and the Second Phase of the Empiricist Level of Analysis - Badeen, Dennis (2012)
This article examines and assesses Bernard Hodgson’s critique of the Neoclassical concept of rationality and its place in the literature. It is argued that Hodgson’s Trojan horse critique is superior to the others because it addresses the role of empiricist epistemology in reducing reason to instrumental rationality and consequent disappearance of the human subject of political economy. The second phase of the empiricist level of analysis reintroduces the capacities for ethical deliberation, self-determination, and the socio-historical conditions and institutional setting of the economic agent. Because Hodgson’s solutions presuppose empiricist terrain, they are arbitrary. This occurs because the fundamental problem of Neoclassical rationality is its ontology. Yet by introducing the human subject into economic theory, Hodgson’s solutions move onto an ontological terrain adequate for economic analysis of human subjects.
Keywords: Trojan Horse; Atomism; Organicism; Neoclassical economics; Rationality; Ontology